Impact of complex mountainous terrain on the development of strong convective storms: A WRF simulation case study in Southeastern Yunnan Province, China - Cong Jiang; Wenjie Jin; Xin Yin; Chen Li; Rui Mao; Liyun Yin (Atmospheric Research, 2026)

Research on global energy efficiency collaborative optimization for wing-diesel hybrid ship based on the improved multi-agent deep deterministic policy gradient algorithm - Cong Wang; Lianzhong Huang; Xiaowu Li; Jianyi Wu; Ranqi Ma; JianLin Cao; Rui Zhang; Haoyang Zhao (Ocean Engineering, 2026)

Preparation of micro-wrapped pyrite-ceramsite fillers for enhancing advanced nitrogen and phosphorus removal in sulfur autotrophic denitrification processes - Cong Ding; Bolin Li; Hongyun Hu; Xiang Li; Xiang Chen; Yingying Yan; Rui Ni; Changying Pei (Journal of Water Process Engineering, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Propylparaben exposure may impair uterine decidualization via FDX1 downregulation and induce preeclampsia-like symptoms in mice - Xiaohui Li; Rui Fu; Huiyu Liu; Yuhan Cai; Cong Zhang (Reproductive Toxicology, 2026)

Oxygen-vacancy-driven dipole ordering and anion anchoring in BaTiO3 nanofibers for high-performance gel polymer electrolytes in high-voltage lithium metal batteries - Yaoxiang Shan; Cong Kang; Bingkun Zang; Ting Li; Bingjia Lu; Rui Sun; Huiying Qu; Xucai Yin; Yang Ren (Chemical Engineering Journal, 2026)

Interface-engineered ZrO2@Co3O4 core-shell materials from bimetallic MOFs for enhanced room temperature NO2 sensing - Jiahui Fan; Xiaopeng Wang; Shanshan Cong; Rui Zhang; Weixin Lv; Li Li; Qingjiang Pan; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Corrigendum to “Preparation of micro-wrapped pyrite-ceramsite fillers for enhancing advanced nitrogen and phosphorus removal in sulfur autotrophic denitrification processes” [J. Water Process Eng. 92 (2026) 110648] - Cong Ding; Bolin Li; Hongyun Hu; Xiang Li; Xiang Chen; Yingying Yan; Rui Ni; Changying Pei (Journal of Water Process Engineering, 2026)

Light heterogeneity shapes contrasting ecological responses to photovoltaic arrays in Tibetan alpine grasslands - Lei Chen; Rui Weng; Wenhao Cong; Shuaihao Bai; Wenping Qin; Qiong Zhao; Saida Li; Yuhan Song; Jingxue Zhao; Lihua Tian (Journal of Environmental Management, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Unpacking asthma risks: A multi-level spatial analysis of social determinants of health in the U.S. - Ming Yan; Cong Fu; Xiao Huang; Siqin Wang; Yuchen Li; Lambed Tatah; Rui Zhu; Yanqing Xu (Applied Geography, 2026)

A Global Optimization Framework for Energy Efficiency of Wing–Diesel Hybrid Ships Under Distinct Sail-Statuses Based on Improved Deep Q-Network and D*Lite Algorithm - Cong Wang; Lianzhong Huang; Xiaowu Li; Ranqi Ma; Jianlin Cao; Rui Zhang; Haoyang Zhao (Journal of Marine Science and Engineering, 2026)
Wing–diesel hybrid ships are a practical approach to sustainable maritime transport that harnesses wind energy to supplement diesel propulsion and reduce carbon emissions. The core optimization problem addressed in this study is the global energy efficiency optimization of path planning and propulsion system cooperative control for wing–diesel hybrid ships under two typical sail operation statuses (sail-deployed and sail-stowed) with dynamic changes in complex maritime meteorological and hydrological conditions. To address this issue, this paper proposes a global energy efficiency optimization framework based on an improved Deep Q-Network (DQN) and D*Lite algorithm. Firstly, the D*Lite algorithm is reconstructed with an incremental replanning mechanism and risk-aware cost function to generate real-time safe path constraints. Secondly, the DQN is improved by adopting a dueling network, noisy exploration and prioritized experience replay, and a differentiated reward function dynamically weighted by sail statuses is designed for it. Finally, a fuel consumption prediction model based on the gradient boosting algorithm is integrated into the reward function to realize an accurate energy efficiency assessment. Empirical results confirm that the framework achieves remarkable carbon reduction effects: the optimized routes reduce the total fuel consumption by 5.02%, cut carbon dioxide emissions by 140.66 tons, and improve the energy efficiency operational index by 7.50%. This framework provides an effective technical solution for the dynamic energy efficiency optimization of wing–diesel hybrid ships under different sail operation statuses.

A general framework for designing and assessing sustainable and diversified cropping systems: Bridging knowledge-driven, model-aided, and participatory approaches - Zhengyuan Liang; Bowen Ma; Rui-Peng Yu; Yuewen Huo; Shingirai Mudare; Feiyu Ying; Long Li; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Performance analysis of an ammonia-kerosene dual-fuel novel SOFC-turboprop engine aviation hybrid system with chemical heat recovery - Xinyan Xiu; Rui Wang; Cong Wang; Jiwei Fang; Meng Zhao; Chenghao Li; Sibo Wang; Jiang Qin; Hongyan Huang (Fuel, 2026)

Electrocatalytic degradation of norfloxacin using biochar electrode derived from oily sludge: Synergistic effects of hydrothermal and pyrolytic treatment - Quxin Cong; Rui Jia; Juan Zhou; Lei Li; Pin Gao (Chemical Engineering Journal, 2026)

Carbon Co-Metabolism enhances anammox enrichment and nitrogen removal in high-rate continuous partial Denitrification–Anammox systems - Rui Du; Cong Li; Shenbin Cao; Yongzhen Peng (Bioresource Technology, 2026)

Diketopiperazines from marine-derived Exserohilum sp. M1-6 - Rui Xu; Jianjian Wang; Changyu Liu; Xuefang Yang; Minjun Chen; Zihan Jin; Shengyan Zheng; Peihai Li; Cong Wang; Shugeng Cao (Natural Product Research, 2026)